Desempenho dinâmico de um trator agrícola utilizando biodiesel destilado etílico e metílico - Soranso, Ana Marta (2006)
The objective of this work was to evaluate the dynamic performance of an agricultural tractor utilizing distilled biodiesel (50% ethylic + 50% methylic) in proportion function of biodiesel and diesel of petroleum (0 and 100%, 5 and 95%, 15 and 85%, 25 and 75%, 50 and 50%, 75 and 25% and 100 and 0%) respectively. This research was done in the area of the department of Rural Engineering of the State University Paulista -UNESP, campus of Jaboticabal - SP, located in the latitude 21º 14 28 S e longitude 48º 17 12 W, and a tractor 4x2 FWA was used, with power of 73,6 kW (100 cv) in the motor and a ballast tractor. The used biodiesel was produced the base of residual oil of fried foods. The experimental design was entirely casualized, with 7 treatments and 5 repetitions, totaling 35 observations. The results evidenced that the mixture, biodiesel and diesel, influenced the variables significantly, hourly volumetric consumption, hourly mass consumption, fuel consumption for worked area and specific fuel consumption. When the tractor operated with 100% of biodiesel (B100) the specific consumption increased 18% on average in relation to the diesel (B0).